Land Snails - Mohammad Effendi, Marzuki; Mohd Zacaery, Bin Khalik; Thor, Seng Liew; Mohd-Azlan, Jayasilan (Natural History Publications (Borneo) Sdn. Bhd., Kota Kinabalu, UNIMAS Publisher, Sarawak Forestry Corporation Sdn Bhd, Kota Samarahan, 2018)
Land snails and slugs belong to the class Gastropoda, within the phylum Mollusca, which is the second most species-rich terrestrial animal phylum, after Arthropoda. Currently at least 25,000 species of land snails and slugs have been described, of which around 1,000 species can be found in Peninsular Malaysia, Sabah, and Sarawak. Unknown to many, the species richness of land snails and slugs is much higher than in other familiar animal groups.